2016
DOI: 10.15244/pjoes/61880
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Relationships between Wheat Cultivars, Fusarium Head Blight, and Mycoflora Grains

Abstract: Stored wheat grains are colonized by a wide range of saprophytic and pathogenic fungi. Contamination by mycotoxigenic species like Fusarium spp. raise concern about the food safety of the commodity. Different environmental and genetic factors govern colonization. The present work studies the relationships between the wheat variety and the resistance against Fusarium head blight (FHB) among the diversity of grain colonizers. Five Swiss and fi ve Polish varieties were planted in an experimental site, and the gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…1 Localities of the sampled populations of Impatiens glandulifera and I. balfourii on the Swiss-Italian border and saprotrophs (Stone et al 2000). Alternaria alternata, Aspergillus niger, Phoma leveillei, Penicillium, and Trichoderma are also classified as secondary pathogens (McRoberts and Lennard 1996;Stone et al 2000;Tekaia and Latgé 2005;Aveskamp et al 2008;Pusz et al 2016). Correlation tests revealed that the number of colonies of C. cladosporioides (secondary pathogen, saprotroph) in non-disinfected seeds correlated negatively with the combined number of colonies of true pathogen species (r S = -0.528, p \ 0.001, N = 36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Localities of the sampled populations of Impatiens glandulifera and I. balfourii on the Swiss-Italian border and saprotrophs (Stone et al 2000). Alternaria alternata, Aspergillus niger, Phoma leveillei, Penicillium, and Trichoderma are also classified as secondary pathogens (McRoberts and Lennard 1996;Stone et al 2000;Tekaia and Latgé 2005;Aveskamp et al 2008;Pusz et al 2016). Correlation tests revealed that the number of colonies of C. cladosporioides (secondary pathogen, saprotroph) in non-disinfected seeds correlated negatively with the combined number of colonies of true pathogen species (r S = -0.528, p \ 0.001, N = 36).…”
Section: Resultsmentioning
confidence: 99%
“…The seeds were inhabited by 14 fungal species, 13 of which were isolated from non-disinfected seeds (Table 2). Four of them were true pathogens of seeds: Fusarium culmorum, F. oxysporum, F. sporotrichoides, and Giberella avenacea (Lemańczyk and Sadowski 2002;Schaafsma et al 2005;Kordas et al 2015;Gołębiowska et al 2016;Pusz et al 2016). Disinfected seeds were attacked by only 6 species (Table 3), only one of which (Cladosporium herbarum) was not found earlier in the non-disinfected seeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These fungi may also constitute an element of the mycoflora that acts as an inhibitor of natural cycles of renewal, since they pose a threat to seedlings and young trees [9], as well as herbaceous plants [38]. Nevertheless, in environments that experience low human disturbance, Fusarium fungi are a regular component of plant communities and, unlike in agricultural crops or nurseries, their incidence is not of epidemic proportion [47].…”
Section: Discussionmentioning
confidence: 99%
“…Even without the occurrence of bioterrorist activities, food contamination is a serious problem [14][15]. Every year in the United States it is the cause of more than 76 million illnesses, 325,000 hospitalizations, and 5,000 deaths.…”
Section: Introductionmentioning
confidence: 99%